GASTROPROTECTIVE AND ANTIOXIDANT EFFECTS OF POWDERED LEAVES OF MORINGA OLEIFERA AGAINST EXPERIMENTALLY INDUCED PEPTIC ULCER IN MALE MICE - N. Latif; M. A. Naeem; A. Rashid; B. Aslam; M. M. Ashraf (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2021)
Moringa oleifera is used worldwide for its different pharmacological actions. In present study, the gastroprotective and antioxidant effects of M. oleifera were investigated in aspirin induced peptic ulcer in adult male mice. For that purpose, sixty healthy adult male mice were divided equally but randomlyinto 6 groups. Blood samples were drawn at 0 and 7 days of treatment. At the termination of experiment, the mice were slaughtered and stomach tissues were excised for histopathological examination. Statistical differences among treatment groups were determined by Duncan’s Multiple Range test at 5% level of significance. The results suggested that aspirin induced gastric mucosal damage significantly (P<0.05) increased the level of total oxidant status and malondialdehyde, while significantly (P<0.05) decreased catalase and total antioxidant capacity. It was concluded that M. oleifera leaves’ powder at the dose rate of 600 mg/kg is as efficacious as omeprazole by exhibiting gastroprotective and antioxidant effects against aspirin induced gastric damage in mice.